2006
DOI: 10.1364/josaa.23.001063
|View full text |Cite
|
Sign up to set email alerts
|

On representing and correcting wavefront errors in high-contrast imaging systems

Abstract: Conventional adaptive-optics systems correct the wavefront by adjusting a deformable mirror (DM) based on measurements of the phase aberration taken in a pupil plane. The ability of this technique, known as phase conjugation, to correct aberrations is normally limited by the maximum spatial frequency of the DM. In this paper we show that conventional phase conjugation is not able to achieve the dark nulls needed for high-contrast imaging. Linear combinations of high frequencies in the aberration at the pupil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…First, we need to understand precisely how the optimum in Fresnel number is impacted by parameters such as size of the DH, number of actuators, type of aperture, and spectral bandwidth. Second, we need to prove that this technique can be used with fixed mirror apodizing techniques (PIAA, PAVC, Guyon et al 2014;Fogarty et al 2017b) (Shaklan & Green 2006;Give'On et al 2006;Pueyo & Kasdin 2007). However, they were usually used to determine surface quality limits of the optics and/or applied to DM optical design in the proposed Michelson interferometer configuration.…”
Section: Resultsmentioning
confidence: 99%
“…First, we need to understand precisely how the optimum in Fresnel number is impacted by parameters such as size of the DH, number of actuators, type of aperture, and spectral bandwidth. Second, we need to prove that this technique can be used with fixed mirror apodizing techniques (PIAA, PAVC, Guyon et al 2014;Fogarty et al 2017b) (Shaklan & Green 2006;Give'On et al 2006;Pueyo & Kasdin 2007). However, they were usually used to determine surface quality limits of the optics and/or applied to DM optical design in the proposed Michelson interferometer configuration.…”
Section: Resultsmentioning
confidence: 99%
“…This was used by Give'on et al [36,37] and new applications may be found in adaptive optics for anti-aliasing spatial filters [40], pyramid wavefront sensing [41], etc.…”
Section: Resultsmentioning
confidence: 99%
“…This happens when the calculated area is limited and/or when a fine sampling is needed. The MFT was first used by Give'on et al [36,37] for the study of wavefront sensing and correction in high-contrast imaging with shaped pupils [38]. We illustrate the case of a point spread function (PSF) calculation with a field of view ( FOV) of 50 resolution elements in Fig.7.…”
Section: The Case Of Direct Imagingmentioning
confidence: 99%
“…The numerical simulations also suggest that extremely small phase aberration less than λ/10,000 rms will be required to achieve the contrast of 10 −10 for detecting extrasolar Earthlike planets. Thus, adaptive optics systems dedicated for highcontrast imagers will play an important role in the terrestrial planet finding missions (Bordé & Traub 2006;Give'on et al 2006;Nishikawa et al 2008). We note that differential imaging techniques can also be used for suppressing the speckle noise (Racine et al 1999;Baba & Murakami 2003;Marois et al 2006;Murakami et al 2006Murakami et al , 2007Zubko et al 2007).…”
Section: Discussionmentioning
confidence: 99%